Technology and Theory of Mechanically Activated Water in Bakery Industry - Sergey D. Rudnev; Tatyana V. Shevchenko; Yulia V. Ustinova; Roman V. Kryuk; Viktor V. Ivanov; Andrey M. Chistyakov (Техника и технология пищевых производств)
Introduction. Bakery products are an important part of traditional Russian menu. Activated water helps to improve the quality of flour products. The present research objective was (1) to activate water with mechanical energy to change the physicochemical properties of the dough; (2) to evaluate the energy efficiency of the new technological process, and (3) to determine the quality indicators of bread. Study objects and methods. The research featured high quality wheat flour, drinking water, and pressed baking yeast (Saccharomyces cerevisiae). Standard research methods were used to assess the physical and chemical properties of water, namely acidity index (pH), surface tension coefficient, and biological activity. The physico-chemical properties of the dough were studied by maximum shear stress and adhesion. Results and discussion. The samples of activated water demonstrated the following technological properties. Its acidity due decreased as pH fell down to 6.05. With a total mixing time of 10 min, the surface tension decreased by about 10%; after 5 min, it decreased by 4%, while the biological activity of activated water increased by 1.5 times. Mechanically treated water used for bread production contributed to the overall energy saving during kneading and increased its water-binding ability. Moisture removal was by 30–40% more intensive than in the control dough sample. Also, the quality of gluten changed as a result of higher shear stress, which gave the experimental dough better forming properties necessary for the production of high-quality bread. The mechanically activated water increased the specific volume of bread from 2.05 to 2.38 cm3/g. Conclusion. The activated water improved the physico-chemical and rheological properties of dough, as well as the main sensory indicators of bread, e.g. porosity and bread crumb elasticity.